The Distribution of Missing Canals in Single-Rooted Teeth with Two Canals - Çulha, Emre; Tunç, Fatma (European Journal of Therapeutics, 2023)
Objective: To determine whether the missing canals in endodontically treated single-rooted teeth with two-canals are present in either buccal or lingual/palatal canals for the Turkish subpopulation. Methods: High-quality cone-beam computed tomography scans of 1297 endodontically treated single-rooted teeth belonging to 782 adults over the age of 18 were obtained from the archive of a dental clinic. Within this dataset, 129 single-rooted teeth had undergone endodontic treatment and possessed two canals, indicating the absence of one canal. These cases included 73 mandibular anterior teeth, 29 mandibular premolars, and 27 maxillary second premolars. We carefully documented both the tooth type and the location of the missing canal. To classify a missing canal as independent, we required it to have a separate orifice from the other canal or be connected to the other canal within 5 mm of its unsealed apex. The differences between categorical variables were tested with Chi-square analysis. P≤0.05 was chosen as the statistical significance level. Results: The buccal canal was missing statistically more often in maxillary second premolars than in other teeth, and mandibular anterior teeth and premolars were statistically similar (p=0.001). The incidence of missing lingual canals was statistically similar in mandibular anterior teeth; and higher compared to maxillary second premolars (p=0.001). Overall, the most frequently missed canal was the lingual canal of the mandibular premolar teeth (96.6%). Conclusions: The prevalence of a missing lingual canal is higher in mandibular anterior teeth and premolars, whereas a missing buccal canal is more frequently encountered in maxillary second premolars. It is essential for clinicians to be aware of these potential morphological variations to enhance the success of root canal treatment.